Mastering Boston Harbor : courts, dolphins, and imperiled waters - Haar, Charles M. (Charles Monroe), 1920-2012 (Harvard University Press, 2005)
This book chronicles how America's most glorious and historically significant harbor was rescued from decades of pollution and neglect by a community of caring citizens who were linked to an environmentally committed judge and his special harbor master. This dynamic public-private team shaped novel legal and political procedures for governing and restoring the harbor.